PENGARUH PROGRAM LITERASI SEKOLAH TERHADAP MINAT BACA DAN PRESTASI BELAJAR SISWA DI SMP ISLAM AL-AZHAAR TULUNGAGUNG - KRISTIANTI LAWALATA, AJENG; SHOLEH, MUHAMAD (Inspirasi Manajemen Pendidikan, 2019)
Abstract: The purpose of this paper was to find out the effect of literacy program on students reading interest and student academic achievement. It used quantitative approach and consisted of three variables, school literacy program (X), students reading interest (Y1) and student academic achievement (Y2). The population of this research were the students of Al-Azhar Tulungagung Islamic Junior High School grade VIII and XI. The total of the population were 270 students and the sample were 157 students. The sample of the study was taken by using stratified random sampling technique. The data collection technique used in this research was questionnaire using likert scale. Test requirements for research data analysis using normality and linearity tests. Data analysis techniques used in this study was simple regression analysis and T test to answer the first and the second hypothesis. Based on the T test, it showed that the significance value of the school literacy program (X) on students reading interest (Y1) was 0,000 <0,05 and the significance value of the school literacy program (X) on student achievement (Y2) 0,000 <0,05. The results of data analysis were as follows: 1) the school literacy program was positive and significant towards students reading interest in Al-Azhaar Tulungagung Islamic Junior High School at 6,899 and 2) the school literacy program was positive and significant for students learning achievement in Al-Azhaar Tulungagung Islamic Junior High School at 2,583. Key words: school literacy program, reading interest, academic achievement. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh program literasi sekolah terhadap minat baca dan prestasi belajar siswa. Pendekatan yang digunakan adalah kuantitatif, terdapat tiga variabel yaitu program literasi sekolah (X), minat baca (Y1) dan prestasi belajar siswa (Y2). Populasi dalam penelitian ini adalah siswa SMP Islam Al-Azhaar Tulungagung kelas VIII dan IX sebanyak 270 siswa dengan sampel 152 siswa. Teknik pengambilan sampel dalam penelitian ini adalah menggunakan teknik stratified random sampling. Teknik pengumpulan data berupa angket atau kuesioner dengan menggunakan skala likert. Uji persyaratan analisis data penelitian menggunakan uji normalitas dan linieritas. Teknik analisis data menggunakan analisis regresi sederhana dan uji T untuk menjawab hipotesis satu dan dua. Hasil penelitian ini menghasilkan kesimpulan berdasarkan uji T bahwa nilai signifikansi program literasi sekolah (X) terhadap minat baca (Y1) adalah 0,000<0,05 dan nilai signifikansi program literasi sekolah (X) terhadap prestasi belajar siswa (Y2) 0,000<0,05. Hasil analisis data adalah sebagai berikut: 1) program literasi sekolah berpengaruh positif dan signifikan terhadap minat baca siswa SMP Islam Al-Azhaar Tulungagung sebesar 6,899 dan 2) program literasi sekolah berpengaruh positif dan signifikan terhadap prestasi belajar siswa SMP Islam Al-Azhaar Tulungagung sebesar 2,583. Kata Kunci: program literasi sekolah, minat baca, prestasi belajar